Correlates of Social Support and its Association With Physical Activity Among Young Adolescents. (April 2018) - Gill, Monique; Chan-Golston, Alec M.; Rice, Lindsay N.; Roth, Sarah E.; Crespi, Catherine M.; Cole, Brian L.; Koniak-Griffin, Deborah; Prelip, Michael L.
Background . A substantial proportion of adolescents, particularly girls and minority youth, fail to meet daily physical activity (PA) recommendations. Social support contributes to adolescent PA, but studies examining this relationship have yielded inconsistent results and rarely focus on diverse, urban populations. Aims . This study examines the correlates of support for PA from family and friends and its relationship with PA outcomes among young adolescents. Methods . Data were collected in a cross-sectional survey of 4, 773 middle school students. Social support from family and friends was separately measured using the Sallis Support for Exercise Scales. Hierarchical logistic regression models were used to assess correlates of high support and the relationship between support and self-reported PA. Results . Approximately one quarter of students reported being active for at least an hour each day. 31.7% of students reported high family support for PA, while 17.8% reported high friend support. Differences in perceptions of support by gender, ethnicity, and language emerged. Support from family and friends were both consistently strong predictors of all three PA outcomes measured. Discussion . Findings highlight the need for multilevel interventions targeting both psychosocial influences on behavior in addition to addressing the physical environment. Given low rates of friend support for PA, there appears to be an opportunity to increase PA levels through promotion of supportive behaviors among peers. Conclusion . Support for PA from family and friends is a key contributor to increased PA among adolescents. Further research is needed to further understand the mechanisms by which these factors influence PA.